KONTRIBUSI KEMAMPUAN MEMBACA APRESIATIF TEKS CERPEN TERHADAP KETERAMPILAN MENULIS TEKS CERPEN SISWA KELAS VII SMPN 26 PADANG - Nengsi, Yendri Surya; Basri, Irfani; Tamsin, Andria Catri (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACTÂ This article has written the contribution of appreciative reading skills in fairy tale texts to the skills of producing short story text in class VII students of SMP 26 Padang. This research is quantitative research using descriptive methods and contribution research designs. The research data is a score of appreciative short story text reading skills and short story text test scores. Data is obtained through two types of tests, namely objective tests that use short story texts that write. Based on the results of data analysis and discussion, the researcher concluded the following three things; first, the average score of appreciative reading skills reads short story texts of students in class VII Padang 26 Junior High School in good qualification (82.01). Second, the average score of short story text students who write students in class VII of Padang 26 Junior High School is in good qualification (79.17). Third, there is a significant contribution between the ability to read short story texts that are appreciative of students who write short story text students in class VII of Padang 26 Junior High School as much as 84.82%.Â Kata Kunci: kontribusi, kemampuan, membaca apresiatif, menulis, teks cerpen